Penanganan Sengketa Ketidaklengkapan Persyaratan Pemilihan Kepala Desa Jaten, Kabupaten Blitar - Cammel Sauqi (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2023)
Based on the 1945 Constitution of the Republic of Indonesia, Indonesia is a unitary state that has a democratic government system. The democratic system in Indonesia is listed in Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Democracy is a form of state implementation system based on people's sovereignty. Democracy is a government of the people, by the people and for the people. The State of Indonesia is a unitary state which is divided into several regions, for example provinces, districts, cities and villages. The embodiment of the democratic system in Indonesia, which has many regions, is by way of the people from each region holding general elections to determine a government.